The use of automated integrated management of childhood illness guidelines in primary health care in the Western Cape in South Africa - Rhode, Hilary Wallis Juliana (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.